Glucocorticoids and Type 2 Diabetes: From Physiology to Pathology - Guido Di Dalmazi; Uberto Pagotto; Renato Pasquali; Valentina Vicennati (Journal of Nutrition and Metabolism)
Type 2 diabetes mellitus is the result of interaction between genetic and environmental factors, leading to heterogeneous and progressive pancreatic β-cell dysfunction. Overweight and obesity are major contributors to the development of insulin resistance and impaired glucose tolerance. The inability of β cells to secrete enough insulin produces type 2 diabetes. Abnormalities in other hormones such as reduced secretion of the incretin glucagon-like peptide 1 (GLP-1), hyperglucagonemia, and raised concentrations of other counterregulatory hormones also contribute to insulin resistance, reduced insulin secretion, and hyperglycaemia in type 2 diabetes. Clinical-overt and experimental cortisol excess is associated with profound metabolic disturbances of intermediate metabolism resulting in abdominal obesity, insulin resistance, and low HDL-cholesterol levels, which can lead to diabetes. It was therefore suggested that subtle abnormalities in cortisol secretion and action are one of the missing links between insulin resistance and other features of the metabolic syndrome. The aim of this paper is to address the role of glucocorticoids on glucose homeostasis and to explain the relationship between hypercortisolism and type 2 diabetes.